Challenges to implementation and strengthening of initial COVID-19 surveillance in Vanuatu: January–April 2020 - Williams, Wendy; van Gemert, Caroline; Mariasua, Joanne; Iavro, Edna; Fred, Debbie; Nausien, Johnny; Manwo, Obed; Atua, Vincent; Pakoa, George Junior; Tassiets, Annie; Knox, Tessa B; Buttsworth, Michael; et al. (Western Pacific Surveillance and Response, 2021)
The Pacific island nation of Vanuatu is vulnerable to emerging infectious diseases, including epidemics and pandemics; chronic food and water insecurity; and natural hazards, including cyclones, earthquakes, tsunamis, landslides and flooding. In March 2020, the World Health Organization characterized the outbreak of novel coronavirus disease 2019 (COVID-19) as a global pandemic. By the end of April 2020, Vanuatu had reported no confirmed cases of COVID-19. Data from several sources are collected in Vanuatu’s COVID-19 surveillance system to provide an overview of the situation, including data from case investigations and management, syndromic surveillance for influenza-like illness, hospital surveillance and laboratory surveillance. Review of data collected from January to the end of April 2020 suggests that there was no sustained increase in influenza-like illness in the community and no confirmed cases were identified. Lessons learnt from the early implementation of surveillance activities, the changing landscape of laboratory testing and pharmaceutical interventions, as well as the global experience, particularly in other Pacific island countries, will inform the refinement of COVID-19 surveillance activities in Vanuatu.